THE ROLE OF STRATEGIC THINKING SKILLS IN DEVELOPING CREATIVE BEHAVIOR-AN EXPLORATORY STUDY OF THE OPINIONS OF LEADERS WORKING AT AL-MUTHANNA UNIVERSITY - Ali Abd Al Razaq Alaboody; Muthana Tawfeeq Abdul-Hassan; Dhrgham Ibrahim AL.Shukri (American Journals, 2024)
The current research aims to identify the role of strategic thinking skills in their dimensions (reflection, systematic thinking, reframing) in developing creative behavior in its dimensions (exploratory creative behavior, investment creative behavior). The research problem was formulated by the main question: Is there a role for strategic thinking in developing creative behavior? Two main hypotheses were formulated, from which several sub-hypotheses emerged to measure the level of correlation and impact by analyzing the relationship between these variables. The research sample consisted of leaders working at Al-Muthanna University, and a questionnaire survey was adopted as the main tool for collecting field-related data. The sample size was 334 individuals, and the data were analyzed using the statistical program (SPSS.V.27). Several conclusions were reached, the most important of which was that strategic thinking skills have a significant correlation and impact on the development of creative behavior. The research concluded with a set of recommendations.
Keywords: Strategic thinking skills, creative behavior.